The Art of Rhetoric / Aristotle - Lawson-Tancred H.C (Penguin Books, 1991)
Few, if any, writers in history have made major contributions to as many fields of knowledge as Aristotle. Preface, Introduction, The Art of Rhetoric, Demonstration, The Genres of Oratory, Deliberation, Constitutions, Emotion and Character, Common Topics, Style, Composition, Universal Aspects, Notes, Bibliography.